Sistema online para alertar riesgos de fuga de gas licuado de petróleo en espacios cerrados Iquitos 2023 - Flores Pacheco Cliver Omar (2024)
Liquefied petroleum gas (LPG) is a fuel commonly used in kitchens for food preparation, and its use has expanded to different sectors, such as industry, transportation, agriculture and for power generation. However, one of the main causes of fires is the leakage of gas in closed spaces, being very dangerous if it is not alerted in time and its expansion is prevented. The proposed research focuses on the implementation and evaluation of preventive measures to mitigate the risk of liquefied petroleum gas leakage in closed environments in the city of Iquitos through the use of a system based on the integration of key components, such as an Arduino UNO board and an MQ6 sensor, which operate in conjunction with a dedicated mobile application. This mobile application and the detector maintain a permanent connection with a cloud server for the continuous transmission of data related to the presence of LPG in the environment. The mobile application allows real-time monitoring, linking with the detector and viewing a history of incidents. When an LPG leak is detected, the system issues an alert via the mobile app and the detector. This solution provides an advanced and effective approach to ensuring safety in confined spaces.